2018
DOI: 10.1631/jzus.b1700063
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of omega-3 polyunsaturated fatty acids against microbial pathogens

Abstract: Microorganisms provide both beneficial and harmful effects to human beings. Beneficial effects come from the symbiotic relationship that exists between humans and microbiota, but then several human illnesses have turned some friendly microbes into opportunistic pathogens, causing several microbial-related diseases. Various efforts have been made to create and utilize antimicrobial agents in the treatment and prevention of these infections, but such efforts have been hampered by the emergence of antimicrobial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 61 publications
1
43
0
1
Order By: Relevance
“…Pathogenic agents can cause infections in different ways, such as through the production of virulence factors and biofilms formation, (Beceiro, Tomás & Bou, 2013;Schroeder, Brooks & Brooks, 2017). In vitro and in vivo studies have demonstrated that omega-3 fatty acids, and in particular linolenic acid and its derivatives, used alone or in combination with conventional antibiotics, possess antimicrobial properties (Chanda et al, 2018). Omega-6, -7, -9 fatty acids, such as γ-linolenic, linoleic, arachidonic, palmitoleic and oleic acids, their ethyl esters and methyl esters, were also shown to be effective against various microorganisms (Huang, George & Ebersole, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic agents can cause infections in different ways, such as through the production of virulence factors and biofilms formation, (Beceiro, Tomás & Bou, 2013;Schroeder, Brooks & Brooks, 2017). In vitro and in vivo studies have demonstrated that omega-3 fatty acids, and in particular linolenic acid and its derivatives, used alone or in combination with conventional antibiotics, possess antimicrobial properties (Chanda et al, 2018). Omega-6, -7, -9 fatty acids, such as γ-linolenic, linoleic, arachidonic, palmitoleic and oleic acids, their ethyl esters and methyl esters, were also shown to be effective against various microorganisms (Huang, George & Ebersole, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs and free fatty acids (FFA) have also been studied for their antimicrobial activity which is characterized by a broad spectrum of activity and the lack of classical resistance mechanisms (Desbois & Smith, 2010;Desbois, 2012;Desbois & Lawlor, 2013). In a recent paper (Chanda et al, 2018), different hypothesis were proposed as PUFAs antimicrobial mode of action which include disruption of intercellular communication, interruption of ATP production, alteration of membrane properties, disruption of fatty acids synthesis, affecting the electron transport system and increasing the number of membrane pores (Zheng et al, 2005;Carballeira, 2008). In addition, as explained elsewhere (Desbois & Smith, 2010), FFAs can also impair Staphylococcus aureus skin colonization through stratum corneum acidification (Fluhr et al 2001;Takigawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This dose was chosen based on prior studies in showing anti-inflammatory effects of n-3 FA in diabetic rats when 500 mg/kg/day were administered [19]. Previous studies found no evidence of toxicity of oral n-3 FA supplementation at 2000 mg/kg/day in rats as summarized in a review by Chanda et al [20]. Prior to surgery, rats were trained for a week to drink from the syringe.…”
Section: Methodsmentioning
confidence: 99%
“…For example, omega-3 FAs play a role in mediating inflammatory processes and immunomodulation for both innate and acquired immune systems [ 9 ]. Also, a study done by Chanda and team concluded that omega-3 FAs could be a potential antimicrobial drug with little potential for drug resistance [ 44 ]. However, the use of these fatty acids as antimicrobial agents has not yet received much attention in clinical medicine worldwide.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%